«La strada continua». Intervista a Mimmo Cuticchio (Mantichora. Italian Journal of Performance Studies, 2020)
We met Mimmo Cuticchio in Palermo, via Bara all’Olivella, in a bright Sicilian morning, herald of spring and we carried on a conversation, begun, in 2015, during Universiteatrali decade’s celebration. There is really no reason to add much more to this introduction, because everybody knows the crucial role played by Cuticchio in the contemporary Italian theatre and, most of all, how he has succeeded in reviving tradition of “cunto”. His wise contribution focuses on a paradox, concerning the ineffable nature of this tradition. Actually, this is the mastery’s key we are looking for and it is no coincidence that we found it in Cuticchio’s work.